Early Renal Vasodilator and Hypotensive Action of Epoxyeicosatrienoic Acid Analog (EET-A) and 20-HETE Receptor Blocker (AAA) in Spontaneously Hypertensive Rats - Walkowska, Agnieszka; Červenka, Luděk; Imig, John D.; Falck, John R.; Sadowski, Janusz; Kompanowska-Jezierska, Elżbieta (Frontiers in Physiology, 2021)
Cytochrome P450 (CYP-450) metabolites of arachidonic acid: epoxyeicosatrienoic acids (EETs) and 20-hydroxyeicosatetraenoic acid (20-HETE) have established role in regulation of blood pressure (BP) and kidney function. EETs deficiency and increased renal formation of 20-HETE contribute to hypertension in spontaneously hypertensive rats (SHR). We explored the effects of 14,15-EET analog (EET-A) and of 20-HETE receptor blocker (AAA) on BP and kidney function in this model. In anesthetized SHR the responses were determined of mean arterial blood pressure (MABP), total renal (RBF) and cortical (CBF) and inner-medullary blood flows, glomerular filtration rate and renal excretion, to EET-A, 5 mg/kg, infused i.v. for 1 h to rats untreated or after blockade of endogenous EETs degradation with an inhibitor (c-AUCB) of soluble epoxide hydrolase. Also examined were the responses to AAA (10 mg/kg/h), given alone or together with EET-A. EET-A significantly increased RBF and CBF (+30 and 26%, respectively), seen already within first 30 minutes of infusion. The greatest increases in RBF and CBF (by about 40%) were seen after AAA, similar when given alone or combined with EET-A. MABP decreased after EET-A or AAA but not significantly after the combination thereof. In all groups, RBF and CBF increases preceded the decrease in MABP. We found that in SHR both EET-A and AAA induced renal vasodilation but, unexpectedly, no additive effect was seen. We suggest that both agents have a definite therapeutic potential and deserve further experimental and clinical testing aimed at introduction of novel antihypertensive therapy.